IDENTIFIKASI PENCEMAR WADUK MANGGAR KOTA BALIKPAPAN - Rezagama, Arya; Syarifudin, Syarifudin; Tamlikha, Ahmad (Jurnal Geografi, 2015)
Manggar reservoirs located in the Village Karangjoang District of North Balikpapan is a major water sourcewith 900 lt/sec. Water quality status of Maggar Reservoir in 2013 showed in heavy polluted condition (BLHBalikpapan, 2013). Water quality measured remains fluctuate where a water quality decline to 4th. To find themain pollution, required the pollutant sources analysis and water capacity of Manggar Reservoir. Sources ofpollution can be natural or anthropogenic. The study used quantitative methods are corroborated by qualitativeanalysis. Debit calculation using rainfall Peanman conversion approach, the analysis capacity of the reservoirusing a guide Minister Of Environmental No. 28 of 2009. The critical peak flow inlet in August at 2.8 m3/sec.While the peak on dry season occurs in August, September and October. The dominant pollution load caused bynatural sources podzolic soil that is acidic and dissolves the high levels of iron in the rocks. This causes afluctuate decrease of oxygen dissolved. While the burden of pollution from human activities is still very smallcompared to the power of purification reservoirs. Water quality reservoir capacity are remain good and on level1. There is a significant effect of the wet and dry conditions on water quality. In the wet season, reservoir waterquality tends to have low oxygen dissolved and high Fe.